Urgensi Kesadaran Sejarah Bagi Peserta Didik - Yusran*, Nurul Fauziah; Riang Tati, Andi Dewi (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
Students should have good historical awareness, as a form of awareness to understand every historical event. History learning is a means of strengthening collective identity, encouraging tolerance, and preventing the repetition of past mistakes. The research study aims to find out how important historical awareness must be possessed by all students as a form of responsibility for history which is embodied in every aspect of their lives. The method used for this research is literature, reviewed from several sources, especially articles related to the writing theme. The research study resulted in an increase in students' history awareness being influenced by the curriculum, educators, methods and use of strategies in learning.